2017
DOI: 10.1021/acs.jmedchem.7b00301
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mixed Pharmacology Melanocortin-3 Agonists and Melanocortin-4 Receptor Tetrapeptide Antagonist Compounds (TACOs) Based on the Sequence Ac-Xaa1-Arg-(pI)DPhe-Xaa4-NH2

Abstract: The centrally expressed melanocortin-3 and -4 receptors (MC3R/MC4R) have been studied as possible targets for weight management therapies, with a preponderance of studies focusing on the MC4R. Herein, a novel tetrapeptide scaffold [Ac-Xaa1 -Arg-(pI)DPhe-Xaa4 -NH2] is reported. The scaffold was derived from results obtained from a MC3R mixture-based positional scanning campaign. From these results, a set of 48 tetrapeptides were designed and pharmacologically characterized at the mouse melanocortin-1, -3, -4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 101 publications
(253 reference statements)
5
50
0
Order By: Relevance
“…An antagonist pA 2 value of 7.3 was observed for KNS2-22-4 at the mMC4R (Figure 3). In prior studies, this compound was observed to possess nanomolar agonist potency at the MC3R (30–40 nM), partial agonist stimulation of the MC4R, and sub-micromolar antagonist potency at the MC4R (pA 2 of 6.6–7) [40,41], similar to the results in the present study.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…An antagonist pA 2 value of 7.3 was observed for KNS2-22-4 at the mMC4R (Figure 3). In prior studies, this compound was observed to possess nanomolar agonist potency at the MC3R (30–40 nM), partial agonist stimulation of the MC4R, and sub-micromolar antagonist potency at the MC4R (pA 2 of 6.6–7) [40,41], similar to the results in the present study.…”
Section: Resultssupporting
confidence: 89%
“…Thus, a DPhe-Arg motif resulted in full agonism at the MC4R and full to partial agonism at the MC3R accompanied by antagonist activity (dependent on the DPhe para -position). Due to the MC3R agonism and MC4R antagonism observed in the Ac-His-Arg-( p I)DPhe-Tic-NH 2 ligand [40,41], it was hypothesized that different substitutions at the DPhe para -position within this scaffold (possessing an Arg-DPhe motif and a Tic residue in position 4) may modulate MC4R agonist efficacy. The results in Table 3 demonstrate that the efficacy at the mMC4R was modulated by various para -substitutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 E and F ). To selectively stimulate MC3R, we administered a previously characterized selective MC3R agonist (C18) ( 30 ) and recorded the neuronal dynamics of PVN MC4R neurons ( Fig. 6 E and F ).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and in vitro characterization of C18 were previously described ( 30 ). C18 was administered via intraperitoneal injection (10 mg/kg, 200 L saline).…”
Section: Methodsmentioning
confidence: 99%